Gastroprotective Chitosan Nanoparticles Loaded with Oleuropein: An In Vivo Proof of Concept - Hend Abd-Allah; John Youshia; Gehad A. Abdel Jaleel; Azza Hassan; Mevidette El Madani; Maha Nasr (MDPI AG, 2024)
Oleuropein is the main constituent of olive leaf extract, and it has shown antioxidant and gastroprotective properties against gastric ulcers. Chitosan nanoparticles are known for their mucoadhesive abilities, and consequently, they can increase the retention time of drugs in the gastrointestinal tract. Therefore, loading oleuropein onto chitosan nanoparticles is expected to enhance its biological efficiency. Oleuropein-loaded chitosan nanoparticles were prepared and characterized for particle size, surface charge, in vitro release, and anti-inflammatory activity. Their in vivo efficacy was assessed by measuring specific inflammatory and protective biomarkers, along with histopathological examination. The optimum oleuropein chitosan nanoparticles were cationic, had a size of 174.3 ± 2.4 nm and an entrapment efficiency of 92.81%, and released 70% of oleuropein within 8 h. They recorded a lower IC50 in comparison to oleuropein solutions for membrane stabilization of RBCs (22.6 vs. 25.6 µg/mL) and lipoxygenase inhibition (7.17 vs. 15.6 µg/mL). In an ethanol-induced gastric ulcer in vivo model, they decreased IL-1β, TNF-α, and TBARS levels by 2.1, 1.7, and 1.3 fold, respectively, in comparison to increments caused by exposure to ethanol. Moreover, they increased prostaglandin E2 and catalase enzyme levels by 2.4 and 3.8 fold, respectively. Immunohistochemical examination showed that oleuropein chitosan nanoparticles markedly lowered the expression of IL-6 and caspase-3 in gastric tissues in comparison to oleuropein solution. Overall, oleuropein chitosan nanoparticles showed superior gastroprotective effects to oleuropein solution since comparable effects were demonstrated at a 12-fold lower drug dose, delineating that chitosan nanoparticles indeed enhanced the potency of oleuropein as a gastroprotective agent.